Art in an algorithm: A taxonomy for describing video game visual styles. (8th February 2018) - Cho, Hyerim; Donovan, Andy; Lee, Jin Ha
Abstract : The discovery and retrieval of video games in library and information systems is, by and large, dependent on a limited set of descriptive metadata. Noticeably missing from this metadata are classifications of visual style–despite the overwhelmingly visual nature of most video games and the interest in visual style among video game users. One explanation for this paucity is the difficulty in eliciting consistent judgements about visual style, likely due to subjective interpretations of terminology and a lack of demonstrable testing for coinciding judgements. This study presents a taxonomy of video game visual styles constructed from the findings of a 22‐participant cataloging user study of visual styles. A detailed description of the study, and its value and shortcomings, are presented along with reflections about the challenges of cultivating consensus about visual style in video games. The high degree of overall agreement in the user study demonstrates the potential value of a descriptor like visual style and the use of a cataloging study in developing visual style taxonomies. The resulting visual style taxonomy, the methods and analysis described herein may help improve the organization and retrieval of video games and possibly other visual materials like graphic designs, illustrations, and animations.